Preliminary Assessment of Methane Concentration Variation Observed by GOSAT in China - Xiuchun Qin; Liping Lei; Zhonghua He; Zhao-Cheng Zeng; Masahiro Kawasaki; Masafumi Ohashi; Yutaka Matsumi (Advances in Meteorology)
Atmospheric column-averaged methane (XCH4) observations from GOSAT are analyzed to study the spatiotemporal variation of XCH4 in China. Furthermore, we investigate the driving mechanism of XCH4 spatiotemporal variations, especially for high XCH4 values shown over Sichuan Basin, by analyzing both the emission mechanism of rice planting process and the regional atmosphere dynamic transportation. The results indicate that spatially the Sichuan Basin presents a higher XCH4 concentration than other regions in China and is 17 ppb higher than the paddy area in the same latitude zone. Seasonally, XCH4 in Sichuan Basin during rice harvest season is generally higher than that in early cultivation period. However, comparing to paddy area in the same latitude zone, Sichuan Basin shows a relatively higher XCH4 value during the winter of noncultivation period when the emissions from rice paddies are weak and surface air temperature is low. To further investigate the high XCH4 concentration during this low-emission period, we use the HYSPLIT model to simulate the atmosphere dynamic transport process, and the result suggests that the typical closed topography of Sichuan Basin, which may lead to CH4 accumulation and keep it from diffusion, is one possible reason for the high XCH4 value in winter.